Blend of Tradition and Modernity in the Select Novels of Anita Nair: A Study on Women Protagonists: Unveiling the Gender Dynamics in Anita Nair's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Anita Nair Is an Indian writer, creative director, and human rights activist. Her works portrays about the social, political, Economic Inequality of the fair sex in the current society. Social inequality should discontinue and economical equalities between both the genders must be maintained. But men receiving more opportunities than women. In Nair’s works one can find the oppression, great insight of solidarity and humour.Women, who constitute half of the world’s population, are always relegated to the secondary status. The phenomenon of subjugation of women is a common feature not only India but in the whole world. Secondary status of a woman has been a silent acceptance for many because, to think of disparity has been considered a ‘sin’ and has a divine sanction as said in religious inscriptions. Women have been oppressed, suppressed and marginalized in every sphere of human activity. Even, a few women at times voiced the paradoxical inequalities and incongruities heaved on them by the patriarchy. Hence, women began to raise their voice in solidarity and sisterhood that began to be a binding bond of their own gender and have been trying to represent and re-present their ‘self.’ through their writings.Since the inception of times every age there is a perilous tussle on the concept of hegemonic identity of the individual surviving in the fore front of the word ‘tradition and modernity’. Tradition surpasses modernity with the passing of time, though conceptually they are complementary necessaries for the development of a society. Tradition or modernity alone is inadequate terminology to exemplify ‘living’ as a philosophy of human survival.